Gate-tunable negative longitudinal magnetoresistance in the predicted type-II Weyl semimetal WTe2 - Yaojia Wang (Nature Portfolio, 2016)
Controllable electric transport of topological particles in solid state systems hold the key towards novel electronic applications. Here, Wang et al. demonstrate gate-tunable negative longitudinal magnetoresistance in WTe2, featuring controllable transport of Type-II Weyl fermions.